Software Engineering on Daily Activities and Fuel Consumption Report at PT. Energate Prima Indonesia - Fahmi Ajismanto; Alan Nuari (Fakultas Ilmu Komputer, Universitas Klabat, 2019)
Software engineering is a field of science which explores device development techniques focusing on the principle of engineering which aims to achieve the objectives of a device that is valuable, efficient and effective in accordance with the needs of users. The probblem that occur in the process of daily activities and fuel consumption report of PT. Energate Prima Indonesia is still conducted conventionally, there is no information system that can support business processes efficiently, lack of security, the reporting process is considered slow for users. The purpose of this research is to develop the software engineering in Daily Activities and Fuel Consumption report at PT. Energate Prima Indonesia. In an effort to help business processes based on user needs. In the software process that is built in this research, used the Spiral model process. The spiral model is the right process to be implemented in the construction of software systems for the Daily Activities and Fuel Consumption Report at PT. Energate Prima Indonesia The stages of the spiral model used in this study are 1. Planning 2. Risk Analysis 3. Engineering 4. User Evaluation. The results of the development software engineering system in daily activities and Fuel Consumption Report at PT. Energate Prima Indonesia has evaluated the results of engineering based on user needs and then performed Software testing using the Black BoX method. Keywords: RPL, Spiral Model, System